NEAR INFRARED LIGHT HEATING OF SOFT TISSUE PHANTOMS CONTAINING NANOPARTICLES - Eibner, S.; Jaime, R. A. O.; Lamien, B.; Basto, R. L. Q.; Orlande, H. R. B.; Fudym, O. (Revista de Engenharia Térmica, 2014)
The objective of this paper is to investigate the effect of the addition of nanoparticles to soft tissue phantoms, aiming at the enhancement of photothermal therapy for cancer. The phantoms were made of Polyvinyl chloride-plastisol (PVC-P), with two different nanoparticles, namely, titanium dioxide nanoparticles (TiO2) and silica nanoparticles (SiO2). A phantom without nanoparticles and a phantom containing a thermal paste were also manufactured for comparison purposes. The PVC-P phantom is transparent to the near infrared laser light, whereas the addition of titanium dioxide nanoparticles modified the optical properties enhancing the local heating, as demonstrated through experiments with a laser-diode and an infrared camera.